Akuntansi Lingkungan BUMDes Mutiara Welirang Untuk Mewujudkan Green Accounting - Erizal Wibisono Santoso; Singgih Bayu Indra Hermawan; Rizky Putra Pratama RIdho (Universitas Multi Data Palembang, 2026)
This study evaluates the implementation of green accounting in a village-owned enterprise (BUMDes Mutiara Welirang, Mojokerto) through its waste-management program and environmental cost treatment. Using a descriptive qualitative case approach, data were collected from interviews with key managers and supporting documents. Analysis triangulates field findings with Environmental Protection Law No. 32/2009, environmental cost concepts, and PSAK 1 stages (identification, recognition, measurement, presentation, and reporting). The BUMDes has operated waste collection and sorting, converted organic waste into maggot-based products and fish feed, and sold recyclable plastics to collectors. However, residual waste is still burned, creating air-pollution risk, and environmental costs are largely aggregated into operating expenses with cash-basis records. Strengthening account classification, budgeting for detection and failure costs, and PSAK-aligned reporting is required to enhance accountability and sustainability.